2016
DOI: 10.1177/0040517516665255
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods for measurement of the pressure exerted by knitted fabrics

Abstract: The article presents the results of measurements of pressure exerted by two model knitted products – bands with different structure (WI jersey weft-knitted fabric and WII openwork warp-knitted fabric). The tests were carried out with using the I-Scan system (in vivo and in vitro tests) and the STM 579 device (in vitro test). A comparative analysis of the in vivo and in vitro results for the I-Scan method and in vitro results for the I-Scan and STM 579 method was performed. It was found that the pressure values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Then, Young’s modulus E is defined as the ratio of engineering stress to engineering strain. 9,5054 So we can write where σ E is the engineering stress (N/mm 2 ), ɛE is the engineering strain and E E is the modulus of elasticity (N/mm 2 ).…”
Section: Derivation Of Mathematical Modelmentioning
confidence: 99%
“…Then, Young’s modulus E is defined as the ratio of engineering stress to engineering strain. 9,5054 So we can write where σ E is the engineering stress (N/mm 2 ), ɛE is the engineering strain and E E is the modulus of elasticity (N/mm 2 ).…”
Section: Derivation Of Mathematical Modelmentioning
confidence: 99%
“…Cieślak et al analyzed the impacts of pressure measurement methods along with two types of knitting structures, i.e., warp knitting and weft knitting, on the compression values using the same materials and concluded that that pressure values were lower in the warp-knitted fabric as compared to the single-jersey weft-knitted fabric in both vivo and vitro tests [ 16 ]. Troynikov et al studied the effects of the physical attributes of warp-knitted tricot and single-jersey weft-knitted products on compression values.…”
Section: Introductionmentioning
confidence: 99%
“…Many research works are focused on orthopaedic supports and analysis of their construction, structure, properties, and behaviour during wearing [7][8][9][10][11][12][13]. Stretchable knitted structures are used for compression garments that contain elastomeric yarns and gain appropriate compression [7].…”
Section: Introductionmentioning
confidence: 99%